In Vivo Assessment the Anti-obesity Potentials of Enteric Lactobacillus spp - Al-Wendawi S.A (Journal of Global Pharma Technology, 2019)
Consumption of probiotics impacted gut microbiota and have potential effects on chronic diseases, such as obesity. This study investigated the anti-obesity potentials of two putative probiotics, Lactobacillus fermentum L1 (Ll) and Lactobacillus paracasei L2 (L2), individually and in combination (L1+L2) against diet-induced obese rats model. The Lactobacillus suspensions were orally administered, to experimental rats, at a daily level, with two consecutives of approximately 1×108 CFU/rat for up to ten weeks. Feeding rats with a combination of L1+L2 was more effective in improvement some of obesity related biomarkers. Rats supplementation with a combination of L1+L2 attenuated the body weight gain in rats that shifted Lee index towered normal value (0.294±0.05).The L1+L2 combinations exhibited hypoglycemic activity, represented by amelioration of glycemic parameters significantly (P<0.05), where, they reduced the levels of; fasting blood glucose (80.43±2.46mg/dl), fasting serum insulin (0.29±0.03ng/dl), and improved insulin resistant disorder (1.05±0.04) comparison with positive control group rats. Concurrently, lactobacilli combinations (L1+L2) pronounced anti- dyslipidemia and improved serum lipid profile of experimental rats, hat the level of blood lipids were significantly (p<0.05) dropped; total cholesterol (TC) to 80.0±2.56 mg/dl, triglycerides (TG) to 79.2±2.07 mg/dl, and low-density lipoproteins cholesterol (LDL-C) to 52.71±2.56 mg/dl. The satiety-related hormones (leptin and adiponectin) levels in rat sera also were altered by supplementation of rats with L1+L2, leptin level was reduced to 1.12±0.05 ng/ml, while adiponectin level was rose to 2.35±0.04 ng/ml.Keywords: Probiotics, Lactobacillus fermentum, Lactobacillus paracasei, Anti-obesity potentials, Dyslipidemias, Glycemic parameters, Leptin and adiponectin.